(untitled) (GEON Journal (Management, Organizations and Business), 2021)
Problematic: The dynamism generated by globalization and the changes proposed by the world context are a call for the general restructuring of all scenarios and especially that related to higher education in Colombia. Objective: Therefore, it is necessary to know the context of higher education in Colombia to understand the alignment with the policies proposed by the governments and the orientations that arise from the world reality in times of pandemic. Materials and methods: Thus, with an exploratory research, a systematic literature analysis was carried out to consolidate the latest guidelines from the authorities in the education sector, considering the rapid development and thematic extension in the field of study. Results: Currently, other educational models different from the traditional one (face-to-face) have been implemented, which include the use of knowledge portals, social networks, and collaborative platforms, taking advantage of the multiple benefits offered by ICT’s and where the Blended Learning methodology has gained greater prominence due to its ability to combine, take advantage of and complement the elements provided by two different environments (physical and virtual). Discussion: In this way, in line with the new demands imposed by the labor market, an education for life is required that involves the development of Soft Skills, considering that soft skills are increasingly necessary to be at the forefront and respond to the demands of the context. Conclusion: Since the reality facing the world has accelerated all transformation processes, causing changes to take place more rapidly and continuously, paradoxically this has become an opportunity to achieve significant advances in education worldwide.